Studies in Modern Islamic Law and Jurisprudence - Arabi, Oussama (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This book shows 19th and 20th century Islamic Law as a dynamic process casting its net into the 21th century and shaping of major constitutional and legal developments in the Arab and Muslim worlds. The introduction and nine chapters of this volume provide insight into the ongoing transformation of the Shari'a into the law of a nation-state. The book contains studies on Marriage and Divorce, Contract Law in the new Civil Codes of Egypt, Iraq and Syria; the ideological springs of Muhammed 'Abduh's visionary program for the reconstruction of Shari'a, the place of Islamic law in the judicial doctrine and policy of the Egyptian State and Legal Capacity.